Despesas em Pesquisa e Desenvolvimento e desempenho de empresas de tecnologia: uma análise multi-países - Lourenço, Victor Haruo Nitatori Rodrigues (Universidade Federal de São Carlos, 2023)
The development of new technologies and production techniques is crucial for companies to gain a competitive advantage, achieved through innovation resulting from Research and Development (R&D). In the context of increasingly global and interconnected markets, where R&D becomes a relevant factor in determining growth and value creation for a company, this study aims to answer the following research question: what is the relationship between the operational performance and future growth expectations of technology companies listed in developed countries and the influence of research and development (R&D) intensity compared to those listed in emerging countries? This study aims to identify whether the country context, such as R&D incentive policies, intellectual property protection, among other factors, influences this relationship. To achieve this, companies in the Information Technology sector were selected, as R&D is essential for maintaining competitiveness in this sector. Companies listed on the top ten stock exchanges by market capitalization in 2021 were chosen, totaling 1,095 companies covering the period from 2012 to 2020. The sample was divided according to the country where the company is listed and according to the company size. The current period R&D intensity, as well as lagged one- and two-year R&D Intensity, were used as predictive variables, along with control variables. Return on Assets (ROA) was selected as the dependent variable to measure operational performance, and Tobin’s q was used to measure market expectations towards the company. The results indicate that companies listed in developed countries have advantages and incentives for R&D expenses, as R&D positively influences operational performance and future market expectations regarding growth opportunities during the expense year and within one year. In contrast, the total sample shows an inverse relationship. Considering emerging countries as well, the relationship is negative, indicating that R&D has a negative impact on both ROA and Tobin’s q in the current year and within one year. This study contributes to the literature by providing insights into the differences between developed and emerging countries, fostering the debate on the need for public policies to mitigate the differences caused by institutional factors in each country. Additionally, the answer to the research question can serve as a basis for company managers to make resource allocation decisions in R&D, indicating the generation of future benefits for the company.
Expenses in Research and Development and performance of technology companies: a cross-country analysis.
Keywords: Pesquisa e Desenvolvimento; Desempenho operacional; Expectativa de mercado; Research and Development; Operational performance; Market expectation; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO FINANCEIRA